User Acceptance of an Electronic Dinar Payment System in Malaysia - Mohd Nazri Muhayiddin; Elsadiq M.A.; Hishamuddin Ismail (2011)
This study is intended to solve several problems associated with physical gold dinar when used as a form of payment. One dinar is equal to 4.25 gram of pure gold. Specifically, this work proposes the use of e-commerce technology -- known as electronic dinar payment system -- to solve those problems. But before actual system can be implemented, this research attempts to find out whether or not the public would be ready to adopt the concept of electronic dinar payment system. The research framework is based on Unified Theory of Acceptance and Use of Technology (UTAUT) (Venkatesh et al., 2003). It measures the user acceptance based on these constructs; performance expectancy, effort expectancy, social influence, and facilitating conditions. In addition, anxiety, perceived credibility, and attitude toward using are added as three new constructs. Data collection is based on a questionnaire survey. From the descriptive analysis results, it is discovered that most of the respondents participated in this survey generally agree with the idea of using the proposed electronic dinar payment system (mean rating of above 4.00).